Correlation between severity of knee osteoarthritis with gender of patients in Secondary Referral Hospital in Indonesia - Panji Sananta; Avicenna Rahmanda; Dhelya Widasmara; Eka Noviya Fuzianingsih (Medicinski glasnik, 2022)
Aim: Knee osteoarthritis is a common osteoarthritis, which limits individual’s activity and affects aspects of daily life and quality of life. The prevalence of osteoarthritis in Indonesians is still high, reaching 12.7% in women and 15.8% in men. Based on the WHO, the prevalence of osteoarthritis in the world is still high, with 18% in women and 80% in men. This study aimed to determine the relationship between gender and the severity of knee osteoarthritis at Baptis Hospital, Batu City. Methods: This cross-sectional study involved 27 female patients and 10 male patients who suffer from knee osteoarthritis at Baptis Hospital, Batu City. Data on gender and the severity of osteoarthritis were collected from medical records. The severity of knee osteoarthritis was assessed using the Kellgren-Lawrence system. Results: Among 27 female (73%) and 10 male patients (27%), seven patients suffered from osteoarthritis grade 1, 13 from osteoarthritis grade 2, 16 from osteoarthritis grade 3, and one patient suffered from osteoarthritis grade 4. There was no significant relationship (p>0.05) between the severity of knee osteoarthritis and patients gender. Conclusion: There was no significant relationship between the severity of knee osteoarthritis between males and females.
Keywords: grade osteoarthritis; joint; Kellgren-Lawrence; quality life; severity